Daytime versus nighttime laparoscopic appendectomy in term of complications and clinical outcomes: A retrospective study of 1001 appendectomies - Amjad A. Shah (17337805) (2022)
Purpose This research aims to study whether the time of day impacts the outcome of laparoscopic appendectomy. Peri/post-operative data including type of surgery, operating room time, length of stay, re-hospitalization rates, and short/long term morbidity and mortality were assembled and analyzed. Methods A retrospective review of all patient's charts who underwent an appendectomy for acute appendicitis at the Acute Care Surgery division at Hamad Medical Corporation (HMC) from December 2017 to July 2020 was performed. Our institution implemented SAGES protocol to patients with laparoscopic appendectomy. Medical history, symptoms, duration of symptoms, type of treatment, complication, experience level of surgeons in different shift, morbidity, mortality, and length of hospital stay were extracted and analyzed. Results Multivariate logistic regression analysis was used to identify the odds ratio (OR) and the correlation of variables with different surgical groups. A total of 1001 patients were included in this study and underwent laparoscopic appendectomy, 51.3% were operated during the daytime shifts and 48.7% during the nighttime shifts. The majority of surgeries were operated during the nighttime shift C (1:00 a.m. to 7:00 a.m.). Neither there was any difference in clinical outcomes nor day/night operation time with physicians. A statistically significant correlation was found between hospital-stay of patients with different surgical group (OR: 2.13, 95% CI: 0.75–0.93, P < 0.001). Conclusion Appendectomy conducted at night is correlated with similar complications as appendectomy performed during the day, and that the varied shift hours had no effect on the complication rates or on the quality of care provided to patients at our hospital. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2022.e11911